Analysis and forecasting of admission indicators of the faculties of Vilnius University (2000–2026) - Jokubaitis, Martynas; Belovas, Igoris (Lietuvos matematikos rinkinys, 2025)
The study investigates the general admission indicators of Vilnius University and its faculties during the 2000–2026 academic years. AR, ARIMA, and exponential smoothing models are applied for data analysis and forecasting. Using correlation analysis, the study aims to assess the impact of demographic factors and determine whether their influence on admission results is statistically significant.
Keywords: ARIMA; forecasting; admission; Vilnius University